Invasive Complete Hydatidiform Moles: Analysis of a Case Series With Genotyping. (March 2016) - Bynum, Jennifer; Murphy, Kathleen M.; DeScipio, Cheryl; Beierl, Katie; Adams, Emily; Anderson, Derek; Vang, Russell; Ronnett, Brigitte M.
Abstract : Complete hydatidiform moles (CHM) are purely androgenetic conceptions, with most (∼85%) arising from fertilization of an egg lacking maternal DNA by a single sperm that duplicates (homozygous/monospermic 46, XX) and a small subset arising via fertilization by 2 sperms (heterozygous/dispermic 46, XY or 46, XX). It remains controversial if heterozygous/dispermic CHMs have a significantly greater risk of persistent gestational trophoblastic disease. Analysis of zygosity of CHMs with and without invasion at presentation, including invasive CHMs with concurrent atypical trophoblastic proliferations concerning for or consistent with choriocarcinoma, has not been specifically addressed. In a prospective series of 1024 products of conception specimens subjected to immunohistochemical analysis of p57 expression and molecular genotyping with short tandem-repeat markers, 288 CHMs were diagnosed, of which 126 were genotyped, including 16 invasive CHMs. Zygosity was compared between those with and without invasion. Of the 16 study cases, 12 (75%) were homozygous/monospermic XX and 4 (25%) were heterozygous/dispermic (3 XY and 1 XX). Of the 110 genotyped noninvasive CHMs, 96 (87%) were homozygous/monospermic XX and 14 (13%) were heterozygous/dispermic (12 XY, 2 XX). Comparison of the zygosity results for the invasive CHMs (study group) with the noninvasive CHMs in the database did not demonstrate a statistically significant difference ( P =0.24, Fisher exact test). In addition, of the 3 cases associated with metastatic gestational trophoblastic disease (pulmonary nodules) at presentation, 2 were homozygous/monospermic XX, indicating that this form is not without risk of significant gestational trophoblastic disease. Thus, the current study has demonstrated a higher frequency of heterozygous/dispermic CHMs among invasive cases compared with those lacking invasion, but does not support the use of zygosity data for risk assessment of CHMs. A persistent, unresolved diagnostic challenge identified in some invasive CHMs is interpretation of accompanying florid atypical trophoblastic proliferations which raise concern for choriocarcinoma. Future studies should address the need for reproducible diagnostic criteria and molecular biomarkers for distinguishing florid hyperplastic from malignant neoplastic trophoblastic proliferations.